Carbon-Ion Radiotherapy for Oral Non-Squamous Cell Carcinoma: Clinical and Radiophysical Perspectives for Indonesia - Ringgit Purbowati; Raditya Faradina (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
Oral non-squamous cell carcinoma (non-SCC) represents a radioresistant malignancy that often responds poorly to conventional X-ray radiotherapy. This resistance creates major clinical challenges, especially in resource-limited settings such as Indonesia. Carbon-ion radiotherapy (C-ion RT) has emerged as an advanced treatment modality that offers superior dose distribution and higher biological effectiveness, making it particularly promising for tumors that are refractory to photon therapy. A systematic narrative review was conducted following the PRISMA 2020 framework. Literature searches in PubMed, Scopus, and ScienceDirect (January 2013-June 2024) used the terms